Implementasi MDLC Dalam Pembuatan Video Profile Sekolah Dasar Negeri 136 Palembang - Aziz, Muhammad Abdul; Ahyar Supani; Fithri Selva Jumeilah (Jurnal Teknologi Informatika Multimedia Digital, 2024)
From the progress of the times that have developed, there are now many ways to spread information from one party to another intended party, especially in promoting something to attract people's attention. Sekolah Dasar Negeri 136 Palembang is one of the elementary schools located at the address Jl. KH. Ahmad Dahlan 26 Ilir, Bukit Kecil District, Palembang City. In doing promotion, Sekolah SD Negeri 136 Palembang already has several forms of promotional media, especially profile video. But the profile video owned by Sekolah SD Negeri 136 Palembang has several weaknesses such as videos that have been made for a long time, unstable videos (have a lot of shaking), poor video quality, and unclear audio volume. So, an update is needed so that the information submitted is more accurate and in accordance with the latest school conditions and can better attract the attention of prospective students and parents of prospective students at Sekolah SD Negeri 136 Palembang